(untitled) (International Journal of Language, Literacy and Translation, 2024)
Language is defined as a means of communication between one person and another for different purposes. Learning it enables individuals to communicate easily with different societies. In addition, it gives a chance to understand their cultures, localities, states, and countries. It also serves as an instrument to share knowledge and experiences. English language becomes the global language in terms of education, technology, science, politics, etc. Report shows that more than half of today’s publications are in English. Hence, this study focuses on the Study of Student-Student Interactions in the English Language Classroom. It selects public senior secondary schools III in Katsina Metropolis. The importance of this study is to investigate whether the level of student-student interactions is enough to facilitate learning. The study reviews different literatures such as collaborative dialogue, peer feedback, question-asking, and the role of a teacher as guide. The study uses social learning theory proposed by Vygostsky (1962). It suggests that learning occurs via interactions students have with their peers, teachers, and other individuals. In that, the learning becomes easier. Also, the teacher stands as a guide to create a good atmosphere for interactions. The instruments for data collection are questionnaires, a target language observation scheme (TALOS) to get information from students, and audio recorded lessons in the schools. Katsina Metropolis has twelve schools, out of which six were selected for the study. The selection is based on the availability of data researchers take into consideration in the schools. Six English language teachers and 132 students are the sample of the study. All six teachers were issued with the questionnaire while 132 students were observed, and the lessons were recorded at different times using the afore-mentioned instruments. For easy comprehension and analysis, the researchers use simple frequency counts and percentages for the analysis of the data collected. The study reveals that student- student interactions in all the schools are very negligible as the students do not utilize them. Hence, it becomes insufficient to facilitate English language learning. It results in having poor results in the future of students, so they cannot further their education. To remedy this problem, schools should enforce the use of English language for every interaction among the students themselves and between the students and the teachers.